Absence of the mitochondrial translocator protein 18 kDa in mice does not affect body weight or food intake responses to altered energy availability. (22nd August 2021) - Morrissey, Nicole A.; Beall, Craig; Ellacott, Kate L. J.
Abstract: Changes in mitochondrial function in a variety of cells/tissues are critical for orchestrating systemic energy homeostasis and are linked to the development of obesity and many of its comorbidities. The mitochondrial translocator protein of 18 kDa (TSPO) is expressed in organs throughout the body, including the brain, liver, adipose tissue, gonads and adrenal glands, where it is implicated in regulating steroidogenesis and cellular metabolism. Prior work from our group and others has shown that, in rodents, TSPO levels are altered in adipose tissue by obesity and that modulation of TSPO activity may impact systemic glucose homeostasis. Furthermore, in vitro studies in a variety of cell types have implicated TSPO in mediating cellular energetics and substrate utilisation. Although mice with germline global TSPO deficiency (TSPO −/− ) have no reported changes in body weight under standard husbandry conditions, we hypothesised that, given the roles of TSPO in regulating mitochondrial function and cellular metabolic flexibility, these animals may have alterations in their systemic response to altered energy availability, either nutritional excess or insufficiency. In agreement with published work, compared to wild‐type (TSPO +/+ ) littermates, TSPO −/− mice of both sexes did not exhibit differences in body weight on standard chow. Furthermore, following a 12‐hour overnight fast, there was no difference in weight loss or compensatory food intake during re‐feeding. Five weeks of feeding a high‐fat diet (HFD) did not reveal any impact of the absence of TSPO on body weight gain in either male or female mice. Basal blood glucose levels and glucose clearance in a glucose tolerance test were influenced by feeding a HFD diet but not by genotype. In conclusion, in the paradigms examined, germline global deletion of TSPO did not change the physiological response to deviations in systemic energy availability at the whole organism level.